Exploring business students’ perceptions of artificial intelligence’s impact on the labor market: a pilot study - Istudor, Nicolae; Dinu, Vasile; Șerban-Oprescu, George-Laurențiu; Badea, Liana; Iacob, Silvia-Elena; Hrebenciuc, Andrei (Journal of Business Economics and Management, 2025)
Artificial intelligence (AI) and its impact on a large array of economic and social facets has recently become one of the most debated topics both in academic and civic environment. Existing literature varies from topics touching on the AI ethics to the future of the labor market. Current research highlights significant divergences and a lack of consensus on the future implications of AI, leading to a heterogeneous perception among the general public. In this context, our research explores the intersection between AI and its profound impact on the labor market, focusing on business students’ perceptions of AI impact on skills, productivity and employment dynamics. The study examines how personal AI competencies, risk perception, and anticipated economic effects of AI technologies shape labor market expectations using structural equations modelling. Seven hypotheses were tested which summarize the correlations between six reflective constructs. Findings reveal that students generally perceive AI positively, recognizing its potential to increase organizational efficiency and work productivity. Our research highlights the dual impact of AI, exploring students’ perceptions of the effects of AI on society, organizations and the labor market and revealing the key links between these views and efficiency.